Experimental Investigation of Using Thermoelectric Coolers under Different Cooling Methods as An Alternative Air Conditioning System for Car Cabin - Sukarno, Ragil; Premono, Agung; Gunawan, Yohanes; Wiyono, Apri; Lubi, Ahmad (Automotive Laboratory of Universitas Muhammadiyah Magelang in collaboration with Association of Indonesian Vocational Educators (AIVE), 2024)
The cabin car temperature will increase when parked in direct sunlight, so the energy required to cool cabin space by the air conditioner will be higher. This study aims to investigate using a thermoelectric cooling system as an alternative to a chiller system to supply cold air to the car cabin under different cooling methods for parked cars. Experimental testing of thermoelectric cooling systems was conducted to produce cold air that can be applied to car cabins as an alternative to conventional air conditioners. The thermoelectric cooling system was varied with single and double TEC modules. The double TEC modules are arranged in a series of electrical and parallel thermal arrangements. A cooling water block using a mixture of water and ethylene glycol with variations of 0.4 lpm, 0.5 lpm, and 0.6 lpm was added to the hot side of the thermoelectric module. The result shows that the thermoelectric cooling system can work properly during the 2-hour test, which constantly supplies air to the cabin space between 20-25 °C, depending on the configuration of the cooling system. The highest COP of 0.84 was obtained when using the double TEC with heatsink and added 0.5 lpm water cooling system, while the lowest COP of 0.53 was obtained when using the single TEC module without a cooling water block.